The mecca of Cold War scholarship: Hong Kong as the intellectual hub to reveal China to the World. Issue 1 (30th July 2020) - Lan, Kenneth
Abstract : Purpose: This writing reveals Hong Kong's role as the center of China research. Before Reform and Opening in 1979, the British colony was the only place in the world where all international China experts stopped over and obtained the latest and the most accurate accounts of PRC. Design/methodology/approach: The paper analyzes how Hong Kong serves as the intellectual mecca through examining the lives of China scholars amid building up their international profiles. What prompted them to join the China field? How were their lives like in the British crown colony? This paper also unveils the roles of the two research institutions played on Communist China studies: University Services Center (USC) and Union Research Institute (URI). In addition to relying on archival correspondences, personal interviews were also conducted in the last two years. Findings: Despite being the mecca of PRC research, Hong Kong was not the first destination for most aspiring China scholars from the West. Most of these Western scholars did not even plan to devote their whole working lives to the study of China. Through luck, draft avoidance and generous grants from Ford and Carnegie Foundations, these young men and women became internationally iconic figures of East Asian research. To complete their Ph.D. theses and subsequent China-related projects, Hong Kong was a "must-go" destination for them. Under the full protection of the Union Jack, these scholars enjoyed the freedom to speak, write, research and publish. God blessed Hong Kong with such a unique political status amid the Cold War. Originality/value: 155 Argyle Street was the Art Deco compound where Red China experts produced most groundbreaking scholarships. It was not only a two-story structure where they acquired their first-hand resources but a platform where any China-related topics were discussed openly under the auspices of British colonial rule of law. Despite claiming themselves as apolitical, both USC and URI were products of US containment policy against communism. Even so, the colonial government never prohibited the two's operations. Through this paper, readers will also discover how young men and women became inspired into a career in China studies.